2001
DOI: 10.1007/s002340000402
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglossal duct cyst carcinoma: case report and review of the literature, with emphasis on CT findings

Abstract: Carcinoma arising in a thyroglossal duct cyst (TDC) is rare. To the best of our knowledge, 155 cases have been reported, 12 of which were studied with CT. The diagnosis is established after surgical excision of the lesion but CT findings may raise the suspicion of malignancy. We present a case of TDC carcinoma and a review of the literature, with emphasis on CT findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 9 publications
1
11
1
2
Order By: Relevance
“…Occurrence of nodules inside the cyst was the most frequent sign of TDCa and calcification, thickness and irregularity of the cyst wall also indicated carcinoma. Nevertheless, no specific radiographic sign can be detected in some cases of TDCa [19]. Only one case in our series has a multicystic appearance in CT.…”
Section: Discussioncontrasting
confidence: 50%
“…Occurrence of nodules inside the cyst was the most frequent sign of TDCa and calcification, thickness and irregularity of the cyst wall also indicated carcinoma. Nevertheless, no specific radiographic sign can be detected in some cases of TDCa [19]. Only one case in our series has a multicystic appearance in CT.…”
Section: Discussioncontrasting
confidence: 50%
“…Thyroglossal duct carcinoma, usually papillary adenocarcinoma, is an uncommon complication of TDC, occurring in less than 1% of cases. [16][17][18] Fistulas are also uncommon in TDCs but can occur after inflammation. 19 Regarding location, our results showed that most of the TDCs were midline, approximately similar to the results of the 2 previous studies (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination usually reveals a firm, nontender, mobile midline mass located at or below the level of the hyoid bone (61%), which rises with protrusion of the tongue. As many as 25%, however, are located laterally, often on the left (14), and others are intrathyroidal (15), intralingual (2%), suprahyoidal (24%), or suprasternal (13%) (16). There is a large differential diagnosis of central cervical cystic lesions, but the most important are cystic degeneration of a benign colloid nodule or an adenoma, papillary carcinoma, or cystic Hashimoto's thyroiditis in the pyramidal lobe.…”
mentioning
confidence: 93%